Influence of repeated sprint exercise on leukocyte morphology in adolescent athletes at different biological maturation rates - Oliveira, F.; Almeida-Neto, P.; Cavalcanti Júnior, G. B.; Ururahy, M. A. G.; Dantas, M. A.; Cabral, B. G. A. T.; Dantas, P. M. S. (Frontiers in Physiology, 2025)
Background: After performing strenuous physical exercises such as repeated sprint exercise (RSE), the leukocyte morphology undergoes changes suggesting immunodepression. Furthermore, it has been previously suggested that, in pediatrics, leukocyte changes may be influenced by the rates of the biological maturation (BM) process, which varies among individuals of similar chronological age.